Serum concentration of vitamin D and sociodemographic characteristics of an elderly population in northeast Brazil (Research, Society and Development, 2021)
In Brazil, the high prevalence of hypovitaminosis D has been observed in several regions and mainly in adults and the elderly. In this context, this study aimed to determine the serum vitamin D concentration and the sociodemographic characteristics of the elderly. This is a cross-sectional study, developed in the year 2017-2018, with 173 elderly people of both sexes, registered in the family health strategy in the city of Teresina - PI, Brazil. The study population was characterized in terms of sociodemographic aspects, with a mean age of 69 years, with a predominance of female, non-Caucasian, married individuals and low education. Regarding lifestyle, the participants were not characterized as smokers and did not even have the habit of consuming alcoholic beverages, on the other hand, a portion was characterized as sedentary, did not use sunscreen and did not expose themselves to the sun. Serum vitamin D concentrations were found to be inadequate among the elderly. Thus, strategies to prevent, detect and treat this vitamin D deficiency need to be incorporated into public health, as changing this profile is necessary, since the deficiency of this vitamin can cause secondary hyperparathyroidism, increased risk of fractures and be related to cognitive impairment and dementia.